Oat germplasm diversity in the world collection held by Plant Gene Resources of Canada - Diederichsen, Axel; Williams, David J.; Richards, Ken W. (MTT, 2004)
Plant Gene Resources of Canada (PGRC) maintains a large germplasm collection of the genus Avena L. with more than 27,000 accessions. The four major groups are: cultivated hexaploid oat (Avena sativa L., including red oat, A. byzantina C. Koch), animated oat (Avena sterilis L.), slender oat (A. barbata Pott ex Link) and wild oat (A. fatua L.). A particular strength of the PGRC collection is the representation of 26 species of the genus Avena. PGRC initiated in 1998 a project to rejuvenate and agrobotanically characterize the oat collection using morphologic, agronomic, disease resistance and quality characters. The recent regeneration of 10,991 A. sativa accessions and the characterization of these accessions allows plant breeders and other scientists to make efficient use of the germplasm in the PGRC collection. The collected data documents the range of phenotypic diversity for a wide range of characters. All data will be made available via the Internet (http://www.agr.gc.ca/pgrcrpc). Different approaches to summarize the characterization data of the hexaploid cultivated oat are presented. Distinct morpho-groups indicating the genetic diversity in the oat collection were defined based on characters which are morphological genetic markers (Rodionova et al. 1994). The genetic diversity in the PGRC oat collection can be quantified by the number of distinct morpho- groups and by the representation of each morpho-group in the collection. It became obvious that certain morpho-groups are dominant in the PGRC collection. Rodionova, N.A. et al. 1994: Flora of cultivated plants, Vol. 2, Part 3, Oat. Kolos, Moscow.
Keywords: Ka; Avena sativa; genebank; genetic diversity; morphology; taxonomy